Growth prospects for the silver economy in the market segment of residential care services provided to dependent elderly people - Iwański, Rafał (Economics and Business Review, 2024)
The aim of this study is to characterise the determinants of the development of the silver economy in the field of care services provided in a residential form for dependent elderly persons in Poland. The analysis was carried out on the basis of statistical and financial background data, including those from the Ministry of Family and Social Affairs, the Ministry of Health, OECD, etc. Although the demand for care services will continue to grow in the coming years, the following barriers to the development of this segment of the silver economy can be identified: lack of employees, unattractiveness of monetary gratification, inefficient financing mechanisms, lack of public investment in the development of care facilities, and increasing costs of providing services in all forms.